The Role of Immunohistochemical Analysis in the Evaluation of EML4-ALK Gene Rearrangement in Lung Cancer. Issue 4 (April 2015) - Sullivan, Harold C.; Fisher, Kevin E.; Hoffa, Anne L.; Wang, Jason; Saxe, Debra; Siddiqui, Momin T.; Cohen, Cynthia
Abstract : Background: Among the mutations described in non–small cell lung carcinoma is a rearrangement resulting from an inversion within chromosome 2p leading to the formation of a fusion gene, echinoderm microtubule-associated protein-like 4-anaplastic lymphoma kinase ( EML4-ALK ). Fluorescence in situ hybridization (FISH) is the gold standard for the detection of ALK gene rearrangements. However, molecular methods are not readily available in all pathology laboratories. Immunohistochemistry (IHC) using an antibody directed against the EML4-ALK fusion protein provides a widely available alternative method of detection. We assessed whether IHC is a comparable and cost-effective alternative to FISH analysis for the detection of ALK gene rearrangements. Design: A total of 110 non–small cell lung carcinoma cases (63 surgical/biopsy and 47 cytology specimens), previously tested for ALK gene rearrangements by FISH [7 (6.4%) positive for the rearrangement], were probed for the EML4-ALK fusion protein using a monoclonal EML4-ALK antibody, clone 5A4. Cells were considered to stain positive for ALK if >5% of cells showed cytoplasmic staining of at least grade 1 intensity (scale: 0 to 3). A cost analysis was performed using ALK IHC as a screening test. Results: The sensitivity and specificity of the EML4-ALK IHC stain compared with ALK FISH analysis were 100% and 96%, respectively. All 7 FISH-positive cases stained positive by IHC, whereas 4 FISH-negative cases demonstrated positive staining. One of the 4 FISH-negative, IHC-positive cases harbored an EML4-ALK rearrangement by RT-PCR yielding 3 false-positive results overall. The κ agreement between IHC and FISH methods is 0.76 (substantial/excellent). The potential savings of implementing the ALK IHC as a screening method would be $10, 418.21. Conclusions: Sensitivity of the EML4-ALK IHC stain is excellent (100%) but due to its suboptimal specificity, IHC cannot reliably supplant FISH analysis for the detection of ALK gene rearrangements. IHC shows promise as a screening tool to prevent unnecessary costly FISH analysis.